Pengaruh Infrastruktur Terhadap Pertumbuhan Ekonomi Di Jawa Tengah Tahun 2012-2014 - AMINAH, EMA NOVIYANTI, Ir. Maulidyah Indira H., MS. (2017)
Improvements in infrastructure will increase investment and the pace of development,good infrastructure will stimulate in increase in people's income,due to increased economic activity a result of the mobility of factors of production and increasing trading activity is high.Some types of infrastructure that needs to be developed to support the growth of the economy and was chosen as a priorityinthe scheme of PPP ( Public Private Partneship ) is transport,roads,irrigation,drinking water and so forth.This Study aimed to determine the effect of infrastructure on economy growth in Central and infrastructure to know where greater influence.The data used is secondary data infrastructure 35 districts/cities in Central Java in the years 2012-2014.Analyzer used in this researchis panel data regression with fixed effect method.The result showed that the variables of health facilities and clean water have a significant effect on economic growth in Java variable mid and educational facilities no significant effect on economic growth in Central Java.